Dry Season Browse Preference for the Black Rhinoceros (Diceros bicornis): the case of the Midlands Black Rhino Conservancy (MBRC), Zimbabwe - Makaure, Joseph; Makaka, Caston (2016)
Dry season browse preference for the black rhinoceros (Diceros bicornis) was studied at the Midlands Black Rhino Conservancy (MBRC), Zimbabwe, in 2010. Free ranging black rhinos were tracked and 8 687 individual bites were recorded at 131 feeding stations and 616 feeding points. Only 34 plant species accounted for the black rhino diet. Trees contributed much of the diet (52.9%) followed by shrubs (44.0%) and lastly herbs (7.3%), with most of the browse (68.7%) coming from the 1.0-1.5m height category. Early dry season diet was richer and more evenly distributed (34 species, H'=3.812.) than late dry diet (27 species, H' =3.413). Acacia nilotica, Acacia karoo, Dichrostachys cineria, Ziziphus mucronata, Lantana camara, Gardenia volkensii and Rhus tenuinervis constituted the principal diet of the rhino, contributing 69.4% and 81.6% of the browse in the early dry and late dry season respectively. In the early dry season L. camara was the most important principal species contributing 32.9% of the browse, scoring the highest proportional usage. (-0.33) and was also the most available (0.26), a position that switched onto A nilotica in the late dry season. The restricted diet obtained in the study may encourage wandering of rhinos into unprotected neighbourhoods making them prone to poaching.